(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Avian influenza is considered as serious global public health problem for poultry industry. Literature suggests that when HPAI/H5N1 Avian influenza (AI) outbreaks, humans are prone to increased risk of transmission. The recent pandemic caused by highly pathogenic AIA (H5N1) in domestic poultry is currently rated phase-3 by the World Health Organization on the pandemic alert scale. Every year 244 species of migratory birds visit Bangladesh in the winter season (October-March) of which approximately 21 species may carry the H5N1 or HPAI (Highly Pathogenic Avian influenza) virus. Objective: To assess socio demographic status and knowledge on mode of transmission of avian influenza among the poultry workers of selected poultry farms in Dhaka city. Materials and Methods: This was a cross-sectional study carried out among the poultry workers of selected poultry farms in Dhaka city. The study was conducted over a period of six months from January 2008 to June 2008. A total of 150 poultry workers aged 9 years and above irrespective of sexes were interviewed face to face by using semi-structured questionnaire. Results: Majority of the respondents were male (92%) and nearly 78% of the respondents had educational level from Class-V to SSC. About three fourth of the respondents (68%) mentioned that avian influenza was transmitted by direct contact. Eighty percent (80%) of the respondents had the knowledge on transmission from poultry to human whereas 63% had the knowledge on transmission from human to human. Good, fair and poor knowledge on mode of transmission of avian influenza was found in 21.33%, 42.67% and 36% of the subjects respectively. Among the respondents belonging to <3 years and 3-5 years duration of service, 12% and 13.33% had poor knowledge followed by 14% and 9.33% had fair knowledge whereas 4% and 4.67% had good knowledge. Conclusion: From the study it was revealed that one third of the workers had poor knowledge on mode of transmission of avian influenza. The study also found that the level of knowledge was found to be good among the older age group having higher educational level and longer duration of service. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 60-65